(untitled) (Acta Scientiarum. Biological Sciences, 2022)
Microbial polysaccharides are of great biotechnological and commercial interest and have wide application in the food, cosmetic and medicine industries. Exopolysaccharide (EPS) production by the yeast Cryptococcus laurentii SD7, isolated from fresh water molluscs, was studied using agro-industrial byproducts as substrates in the submerged fermentation. The Central Composite Design (CCD) 23 was used to study the influence of pH, different concentrations on sugarcane molasses and corn steep liquor (CSL), for 48 hours. According to the results, the highest EPS production occurred at the initial pH 5 and at 8.4% concentration of sugarcane molasses, which were statistically significant variable at 10% (p < 0.1). The concentration of CSL had no influence in the studied range, thus, it can be used lowest concentration (0.3%). The time course of EPS production showed that while cell growth peaked within 48 hours, the highest EPS production (6.61 g L-1) occurred at 168 hours, with a productivity of about 0.04 g L-1 h-1. The pH of the medium remained approximately constant throughout the fermentation process. The yeast C. laurentii SD7 showed great potential for EPS production at a low cost and with sustainable substrates.